Increasing fruit and vegetable intake on low-income population in Vietnam and Nigeria through food systems innovations - Nigeria Market Level Assessment Report - Shittu, Oluyemisi O.; Adeyemo, Temitayo; Samuel, Folake (2021)
Using retailer sample from two market (180 retailers) and two neighborhood (87 retailers) locations, this Market Level Assessment (MLA) reveals overlaps and parallels in retailer characteristics, business modules as well as returns on investment. The MLA was carried out across four fruit and vegetable groups peculiar to the Nigerian environment namely Dark Green Leafy Vegetables (DGLV), Vitamin A Rich Fruits (VARF), Other Fruits (OF) and Other vegetables (OV).